Rapid screening of UPB1 gene variations by high resolution melting curve analysis - Xu, Xiaowei (Exp Ther Med, 2021)
The present study aimed to analyze gene mutations in patients with β-ureidopropinoase deficiency and establish a rapid detection method for β-ureidopropinoase (UPB1) pathogenic variations by high resolution melting (HRM) analysis. DNA samples with known UPB1 mutations in three patients with β-ureidopropinoase deficiency were utilized to establish a rapid detection method for UPB1 pathogenic variations by HRM analysis. Further rapid screening was performed on two patients diagnosed with β-ureidopropinoase deficiency and 50 healthy control individuals. The results showed that all known UPB1 gene mutations can be analyzed by a specially designed HRM assay. Each mutation has specific HRM profiles which could be used in rapid screening. The HRM method could correctly identify all genetic mutations in two children with β-ureidopropinoase deficiency. In addition, the HRM assay also recognized four unknown mutations. To conclude, the results support future studies of applying HRM analysis as a diagnostic approach for β-ureidopropinoase deficiency and a rapid screening method for UPB1 mutation carriers.